DEFISIT PERAWATAN DIRI PADA PASIEN SKIZOFRENIA DI RUMAH SAKIT JIWA PROF. DR V.L RATUMBUYSANG MANADO - Kaghoo, Noifke; Massa, Kartini; Mangundap, Lavenia Y. (Yayasan Syalom Cipta Sumikolah, 2024)
The role of mental health nurses is to provide care to schizophrenic patients who experience self-care deficits by teaching patients to be able to meet their self-care needs again or without help. Provide support to fulfill self-care requirements and teach the importance of personal hygiene such as bathing, grooming and dressing. This study aims to determine the description of the self-care deficit in schizophrenia patients at the Prof. Dr. V. L Ratumbuysang Mental Hospital, North Sulawesi Province. This type of research is descriptive observational with a cross-sectional approach, on a sample of 54 schizophrenia patients who were undergoing treatment. The results of the study showed a self-care deficit in schizophrenia patients at the Prof.Dr.V.L Ratumbuysang Mental Hospital, North Sulawesi Province. Most of the levels of independence were capable with assistance, there were 36 people (66.7%), able without assistance, there were 13 people (24.1%) and those who had not 5 people (9.3%) can afford it. Conclusion: The self-care deficit in schizophrenia patients at the Prof. Dr. 9.3%). It is recommended for health workers, especially nurses, to always support patients by providing group activity therapy (TAK), supportive and cognitive group therapy to provide stimulus to meet the self-care needs of schizophrenia patients.